An Analysis of Hainan Province Tourism Development - Wenbo Lyu; Yuxin Wang (Theoretical Key Issues and Practical Development Trends of China’s Digital Economy, 2024)
Yalong Bay International Rose Valley Scenic Spot in Sanya is a comprehensive tourist destination that combines the beauty of nature and humanistic feelings. With the core theme of "beauty, romance and love", relying on the natural features of farmland, reservoir and mountain forest, and centered on colorful roses, it has created a large-scale comprehensive scenic spot integrating rose planting, cultural display and tourism and leisure. It is the largest rose valley in Asia. As a tourist city in China, Sanya’s tourism industry has contributed significantly to its GDP. In recent years, tourism revenue has been accounting for more than 60% of Sanya’s GDP. Although the COVID-19 pandemic has reduced the proportion since 2020, tourism revenue still accounts for more than 50 percent of Sanya’s GDP. It is crucial to reinforce governmental oversight, enhance the tourism service framework, fortify the monitoring of the corporate marketplace, and propel Hainan’s tourism sector to an elevated echelon. By integrating our unique regional culture into this process and crafting a distinct tropical island brand persona, can significantly augment Hainan’s GDP.